Dukungan Keluarga Mempengaruhi Kelengkapan Imunisasi Dasar Pada Bayi dan Balita - Lushinta, Lidia; Patty, Fara Imelda Theresia; Anggraini, Eliza; Putri, Rosalin Ariefah (Jurusan Kebidanan Poltekkes Kemenkes Mamuju, 2024)
The morbidity and mortality rates of children can indicate the health status of a country. Immunization is one of the programs suggested to improve health status. The success of these programs can be observed by the achievement of UCI (Universal Child Immunization) from the coverage of complete essential immunization. The rejection of vaccination from families is one of the most common reasons why children don't receive complete immunization. Other reasons include busy schedules, remote locations, and frequent illnesses. These factors influence parents to reject or receive particular immunization programs or vaccines, including support factors from the family. The support from family can come in various forms such as providing motivation, offering guidance, or monitoring daily intake of food and medication. This study determines the relationship between family support and the completeness of essential immunization in infants and toddlers. The type of research used is descriptive research with a quantitative approach method and cross-sectional design. The technique used in this research is purposive sampling. The results showed that there is a relationship between family support and the completeness of essential immunization for infants and toddlers. Health workers are recommended to actively involve families by increasing their knowledge about the importance of complete immunization.